Pengetahuan Masyarakat Pulo Gebang Permai Tentang Produk Perbankan Syariah - Adelia, Sisi; Salma, Hartini; Fajar, Ade (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2024)
This research used a combination of interviews, qualitative methods, and literature review to achieve its objectives. Primary data was obtained through interviews conducted with the community, while secondary data came from relevant books and theses. The collected data was analyzed using qualitative descriptive methods, and subsequent discussion produced deductive conclusions based on the research results. This research aims to achieve two main objectives: first, to assess the level of knowledge of the Pulo Gebang Permai community about sharia banking products, and second, to identify the factors that influence their knowledge about these products. The results of this research reveal that public understanding of sharia banking products in Pulo Gebang Permai is still limited, with the main contributing factor being the lack of adequate outreach efforts from banking institutions. Improving communication and education is very important to not only increase awareness, but also promote a deeper understanding of the products offered by banks that are in accordance with sharia principles. This means that economics in Islam is a science that studies everything in life and of course also has a purpose. Bearing in mind the development of sharia banking in Pulo Gebang Permai so far the level of public knowledge in understanding sharia banking products is still minimal, this requires efforts from the sharia banking side and apart from good promotions, it must also change the public's view of sharia banks.